Asphalt-based silicon-carbon composite material, preparation method thereof and lithium ion battery

By doping lithium hydride in the asphalt-based porous carbon precursor and covering the organic lithium compound, a three-layer core-shell structure asphalt-based silicon-carbon composite material was prepared, which solved the problems of low efficiency and power performance deviation of lithium-ion batteries for the first time, and achieved the improvement of high efficiency and stable performance.

CN119542404APending Publication Date: 2025-02-28BEIJING SOLIDE NEW MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411831934.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, as the negative electrode auxiliary material, the first-time efficiency of the lithium-ion battery is low and its power performance deviation is insufficient when preparing the silicon-carbon composite material.

Method used

By doping lithium hydride in the asphalt-based porous carbon precursor to generate metal lithium doped porous carbon, and coated the outer layer with an organolithium compound, secondary coating is achieved to obtain an asphalt-based silicon-carbon composite material with a three-layer core-shell structure.

Benefits of technology

The electronic conductivity and ion diffusion coefficient of the material are improved, the first-time efficiency and rate performance are improved, and the stability and performance of the material are improved through a three-layer core-shell structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542404A_ABST
    Figure CN119542404A_ABST
Patent Text Reader

Abstract

The invention relates to an asphalt-based silicon-carbon composite material, a preparation method thereof and a lithium ion battery. The preparation method comprises the following steps: providing pitch coke, sodium hydroxide and lithium carbonate, uniformly mixing the raw materials, calcining in a nitrogen atmosphere, sequentially washing with mixed acid and deionized water after calcining, and carrying out vacuum drying to obtain pitch-based porous carbon; adding the pitch-based porous carbon into a vacuum furnace, and respectively introducing heteroatom gas, silane gas and metal compound gas in stages to obtain a metal-doped silicon-carbon precursor material; and heating the metal-doped silicon-carbon precursor material, introducing oxidizing mixed gas for passivation, soaking the passivated metal-doped silicon-carbon precursor material in an organic solvent of an organic lithium compound, uniformly mixing, and carrying out spray drying to realize secondary coating, thereby obtaining the asphalt-based silicon-carbon composite material. The asphalt-based silicon-carbon composite material has a three-layer core-shell structure, so that the stability and the performance of the material are improved, and the first efficiency and the power performance of the material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to an asphalt-based silicon-carbon composite material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] In modern society, with the rapid development of portable electronic devices, electric vehicles and renewable energy systems, the demand for lithium-ion batteries with high energy density and high power density is increasing. Lithium-ion batteries have become the main energy storage devices due to their advantages such as high energy density, long cycle life and low self-discharge rate. Current lithium-ion batteries use graphite, silicon and silicon-carbon composite materials as negative electrode materials.

[0003] The current new silicon-carbon materials are mainly composed of biomass or resin-based porous carbon as the matrix, and nano-silicon in its pores. Due to the poor consistency of biomass porous carbon and the uncontrollable quality of its raw materials, and the large pores inside the material cause its local expansion to be large, and the high price of resin-based porous carbon due to the use of resin to form pores, the price of the silicon-carbon materials prepared is relatively high. Asphalt, as a negative electrode auxiliary material, has been used as a coating or granulation material in graphite materials. It has a wide range of material sources, low cost, good stability, and good isotropy of the material, which makes the material have better dynamic properties and compaction density. However, as a raw material for preparing porous carbon, there are defects such as high difficulty in forming pores, difficult process control, and low initial efficiency.

[0004] For example, patent CN202410250702.9 discloses: a method for preparing silicon-carbon composite materials based on silane cracking method and its application, wherein the preparation method is as follows: S1) petroleum coke and inorganic carbonate compounds are put into a reaction chamber, and modified gas is introduced for carbonization to obtain porous carbon of petroleum coke; S2) silane gas and heteroatom gas are introduced for vapor deposition to obtain heteroatom-doped silicon-carbon precursor material; S3) surface passivation and fluorination gas are used for vapor deposition to obtain silicon-carbon composite materials. Although the obtained silicon-carbon composite material has the advantages of low cost and low expansion, the lithium-ion battery made of the silicon-carbon composite material has the disadvantages of low initial efficiency and power performance deviation.

[0005] Therefore, it is necessary to improve the prior art. Summary of the invention

[0006] In the prior art, when asphalt is used as a negative electrode auxiliary material in the technology of preparing silicon-carbon composite materials, the obtained lithium-ion batteries still have shortcomings such as low initial efficiency and power performance deviation. Therefore, the present invention provides an asphalt-based silicon-carbon composite material and a preparation method thereof, and a lithium-ion battery for solving the above problems.

[0007] To achieve the above object, in a first aspect, the present invention provides a method for preparing a pitch-based silicon-carbon composite material, which comprises the following steps: S1. The raw materials are mixed evenly according to the mass ratio of pitch coke: sodium hydroxide: lithium carbonate = 100: (100-200): (10-50), calcined under a nitrogen atmosphere, washed with mixed acid and deionized water in sequence after calcination, and vacuum dried to obtain pitch-based porous carbon; S2, adding the asphalt-based porous carbon into a vacuum furnace, and introducing heteroatom gas, silane gas, and metal compound gas in stages to obtain a metal-doped silicon-carbon precursor material; S3, heating the metal-doped silicon-carbon precursor material and introducing an oxidizing mixed gas for passivation, and after passivation, immersing it in an organic solvent of an organic lithium compound, mixing it evenly and spray drying it to achieve secondary coating, thereby obtaining the asphalt-based silicon-carbon composite material.

[0008] In one implementation, in S1, the calcination temperature is 600-1100° C., and the calcination time is 2-6 hours; the mixed acid is hydrochloric acid and nitric acid in a volume ratio of 1:1, and the concentration of the mixed acid is 8-12%.

[0009] In one implementation, in S2, the specific steps include: S21, adding the asphalt-based porous carbon into a vacuum furnace, introducing nitrogen and maintaining the pressure in the furnace at 1-5 MPa, and introducing heteroatom gas at a flow rate of 50-200 ml / min for 30-300 min when heated to 900-1200° C.; S22, after cooling to 450-550°C, introduce silane gas at a flow rate of 100-500 ml / min for 60-600 min; S23, after heating to 850-1100°C, introduce metal oxide gas at a flow rate of 50-200 ml / min for 60-600 min to obtain a metal-doped silicon-carbon precursor material.

[0010] In one implementation, in S2, the heteroatom gas is any one of ammonia, hydrogen sulfide, phosphine and borohydride; the silane gas is any one of monosilane, disilane, trichlorosilane and dimethylchlorosilane; the metal compound gas is any one of lithium hydride, magnesium hydride and aluminum hydride.

[0011] In one implementation, in S3, the temperature of the passivation process is 100-200°C, the introduction rate of the oxidizing mixed gas is 10-100 ml / min, and the passivation time is 30-300 min.

[0012] In one implementation, in S3, the oxidizing gas is a mixture of any one of O2, O3 and SO2 and nitrogen, and the volume ratio thereof is (1-5):10.

[0013] In one implementation, in S3, the organic lithium compound is any one of lithium sulfonate, lithium amide, lithium acetate, lithium stearate and lithium pyruvate; and the organic solvent is any one of propylene carbonate, dimethyl carbonate and diethyl carbonate.

[0014] In a second aspect, the present invention further provides a pitch-based silicon-carbon composite material, which is prepared by any one of the preparation methods of the pitch-based silicon-carbon composite materials described above.

[0015] In one implementation, the asphalt-based silicon-carbon composite material has a three-layer core-shell structure, wherein the core is a metal-doped silicon-carbon material, the middle layer is silicon dioxide, and the outer shell is an organic lithium compound, comprising the following mass ratio of the core: middle layer: outer shell = (93~98.5): (0.5~2): (1~5).

[0016] In a third aspect, the present invention further provides a lithium-ion battery, which comprises the above-mentioned asphalt-based silicon-carbon composite material as a negative electrode material.

[0017] Beneficial effects: The asphalt-based silicon-carbon composite material provided in the present invention can improve the electronic conductivity of the material, reduce polarization, and improve the specific capacity and its first efficiency by doping lithium hydride into the asphalt-based porous carbon precursor. By coating the outer layer with an organic lithium compound, the ion diffusion coefficient of the material can be improved, and the first efficiency and its rate performance can be improved. The asphalt-based silicon-carbon composite material obtained by the present invention presents a three-layer core-shell structure, which helps to improve the stability and performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a flow chart of the steps of the method for preparing the asphalt-based silicon-carbon composite material provided by the present invention; Figure 2 This is a SEM image of the asphalt-based silicon-carbon composite material provided in Example 1.

[0019] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0021] See also Figure 1 , Figure 1 The present invention provides a method for preparing a pitch-based silicon-carbon composite material, which comprises the following steps: S1. The raw materials are mixed evenly according to the mass ratio of pitch coke: sodium hydroxide: lithium carbonate = 100: (100-200): (10-50), calcined under a nitrogen atmosphere, washed with mixed acid and deionized water in sequence after calcination, and vacuum dried to obtain pitch-based porous carbon; S2, adding the asphalt-based porous carbon into a vacuum furnace, and introducing heteroatom gas, silane gas, and metal compound gas in stages to obtain a metal-doped silicon-carbon precursor material; S3, heating the metal-doped silicon-carbon precursor material and introducing an oxidizing mixed gas for passivation, and after passivation, immersing it in an organic solvent of an organic lithium compound, mixing it evenly and spray drying it to achieve secondary coating, thereby obtaining the asphalt-based silicon-carbon composite material.

[0022] The present invention obtains a precursor material by depositing heteroatoms, nano silicon and metallic lithium in stages, and performs passivation and organic lithium coating to obtain a silicon-carbon composite material, thereby improving the initial efficiency and power performance of the material.

[0023] Specifically, in S1, the calcination temperature is 600-1100°C, the calcination time is 2-6 hours, the mixed acid is hydrochloric acid and nitric acid in a volume ratio of 1:1, and the concentration of the mixed acid is 8-12%. The pitch coke is preferably a raw material with a particle size of 5-10 μm after crushing.

[0024] Specifically, in S2, the specific steps include: S21, adding the asphalt-based porous carbon into a vacuum furnace, introducing nitrogen and maintaining the pressure in the furnace at 1-5 MPa, and introducing heteroatom gas at a flow rate of 50-200 ml / min for 30-300 min when heated to 900-1200° C.; S22, after cooling to 450-550°C, introduce silane gas at a flow rate of 100-500 ml / min for 60-600 min; S23, after heating to 850-1100°C, introduce metal oxide gas at a flow rate of 50-200 ml / min for 60-600 min to obtain a metal-doped silicon-carbon precursor material.

[0025] In one implementation, in S2, the heteroatom gas is any one of ammonia, hydrogen sulfide, phosphine and borohydride; the silane gas is any one of monosilane, disilane, trichlorosilane and dimethylchlorosilane; the metal compound gas is any one of lithium hydride, magnesium hydride and aluminum hydride.

[0026] Specifically, in S3, the temperature of the passivation process is 100-200°C, the introduction rate of the oxidizing mixed gas is 10-100 ml / min, and the passivation time is 30-300 min. The oxidizing gas is a mixture of any one of O2, O3 and SO2 and nitrogen, and the volume ratio is (1-5):10. The organic lithium compound is any one of lithium sulfonate, lithium amide, lithium acetate, lithium stearate and lithium pyruvate; the organic solvent is any one of propylene carbonate, dimethyl carbonate and diethyl carbonate. Among them, the metal doping in S2 and the secondary coating in S3 improve the mechanical strength and durability of the composite material and reduce the structural damage during the charge and discharge process.

[0027] In the second aspect, the present invention also provides an asphalt-based silicon-carbon composite material, which is prepared by any of the above-mentioned preparation methods of the asphalt-based silicon-carbon composite material. The asphalt-based silicon-carbon composite material has a three-layer core-shell structure, wherein the core is a metal-doped silicon-carbon material, the middle layer is silicon dioxide, and the outer shell is an organic lithium compound, including the following mass ratio of the core: middle layer: outer shell = (93~98.5): (0.5~2): (1~5). The asphalt-based silicon-carbon composite material obtained by the present invention has a three-layer core-shell structure, which helps to improve the stability and performance of the material; at the same time, due to its unique structure and composition, this composite material exhibits excellent electrochemical properties in lithium-ion batteries, including high capacity and long cycle life.

[0028] Example 1 This embodiment provides a method for preparing a pitch-based silicon-carbon composite material, comprising the following steps: S1. Take 100 g of asphalt coke with a particle size of 8 μm after crushing, 150 g of sodium hydroxide and 30 g of lithium carbonate, mix them evenly, transfer them to a tube furnace, heat them to 900° C. under a nitrogen atmosphere and keep them warm for 4 hours, then wash the obtained material with a 10% mixed acid, wherein the mixed acid is hydrochloric acid and nitric acid in a volume ratio of 1:1, then wash with deionized water, and vacuum dry them at 80° C. for 24 hours to obtain asphalt-based porous carbon; S2. Add asphalt-based porous carbon into a vacuum furnace, introduce nitrogen to exhaust the air in the pipe, and maintain the pressure of the cavity at 3Mpa. First, heat it to 1100°C, and then introduce ammonia gas at a flow rate of 100ml / min for 150min; then cool it to 500°C, and change to monosilane gas, and introduce it at a flow rate of 300ml / min for 150min; then raise the temperature to 950°C and introduce lithium hydride gas, and introduce it at a flow rate of 100ml / min for 150min to obtain a metal-doped silicon-carbon precursor material; S3. Heat 100g of the metal-doped silicon-carbon precursor material to 150°C, and introduce a mixed oxygen gas (volume ratio, oxygen:nitrogen = 2:10) at a flow rate of 50ml / min for 150min for passivation. Then, immerse it in an organic solvent of propylene carbonate with a mass concentration of 300g and a mass concentration of 1wt% lithium sulfonate to mix evenly, spray dry it, and achieve secondary coating to obtain an asphalt-based silicon-carbon composite material.

[0029] Example 2 This embodiment provides a method for preparing a novel asphalt-based silicon-carbon composite material, comprising the following steps: S1. Take 100 g of asphalt coke with a particle size of 5 μm after crushing, 100 g of sodium hydroxide and 10 g of lithium carbonate, mix them evenly, transfer them to a tube furnace, heat them to 600 ° C in a nitrogen atmosphere and keep them warm for 6 hours, then use 500 g of 10% mixed acid (volume ratio, hydrochloric acid: nitric acid = 1:1) for washing, deionized water for washing, and vacuum dry them at 80 ° C for 24 hours to obtain asphalt-based porous carbon; S2, adding the asphalt-based porous carbon into a vacuum furnace, and introducing nitrogen to exhaust the air in the pipe, and maintaining the pressure of the cavity at 1Mpa, first heating to 1200°C, and then introducing hydrogen sulfide gas at a flow rate of 50ml / min for 300min; then cooling to 550°C, changing to disilane gas, and introducing it at a flow rate of 100ml / min for 600min; then heating to 1100°C and introducing magnesium hydride gas, and introducing it at a flow rate of 50ml / min for 300min to obtain a metal-doped silicon-carbon precursor material; S3. Heat 100g of the metal-doped silicon-carbon precursor material to 100°C and introduce a bromine-oxygen mixed gas (volume ratio, bromine-oxygen: nitrogen = 1:10) at a flow rate of 10ml / min for 300min for passivation. Then, immerse the obtained material in 100g of dimethyl carbonate organic solvent with a mass concentration of 1wt% lithium amide, mix evenly, spray dry, and achieve secondary coating to obtain an asphalt-based silicon-carbon composite material.

[0030] Example 3 This embodiment provides a method for preparing a novel asphalt-based silicon-carbon composite material, comprising the following steps: S1. Take 100 g of asphalt coke with a particle size of 10 μm after crushing, 200 g of sodium hydroxide and 50 g of lithium carbonate, mix them evenly, transfer them to a tube furnace, heat them to 1100° C. under a nitrogen atmosphere and keep them warm for 2 h, then wash them with 500 g of 10% mixed acid (volume ratio, hydrochloric acid: nitric acid = 1:1), wash them with deionized water, and vacuum dry them at 80° C. for 24 h to obtain asphalt-based porous carbon; S2, adding the asphalt-based porous carbon into a vacuum furnace, and introducing nitrogen to exhaust the air in the pipe, and maintaining the pressure of the cavity at 5 MPa, first heating to 900°C, and then introducing phosphine gas at a flow rate of 200 ml / min for 30 minutes; then cooling to 450°C, changing to trichlorosilane gas, and introducing it at a flow rate of 100 ml / min for 600 minutes; then heating to 850°C and introducing aluminum hydride gas at a flow rate of 200 ml / min for 30 minutes to obtain a metal-doped silicon-carbon precursor material; S3. Heat 100g of the metal-doped silicon-carbon precursor material to 200°C and introduce a sulfur dioxide mixed gas (volume ratio: sulfur dioxide gas: nitrogen = 3:10) at a flow rate of 100ml / min for 30min for passivation. Then, immerse the obtained material in 500g of diethyl carbonate organic solvent with a mass concentration of 1wt% lithium acetate, mix evenly, spray dry, and achieve secondary coating to obtain an asphalt-based silicon-carbon composite material.

[0031] Comparative Example 1 The difference from Example 1 is that lithium carbonate is not added in step S1, and the rest is the same as Example 1.

[0032] Comparative Example 2 Different from Example 1, commercially available biomass porous carbon (manufacturer: Japan Kuraray Co., Ltd., model, YP-50F) is used to replace the asphalt-based porous carbon.

[0033] Comparative Example 3 The difference from Example 1 is that lithium hydride gas is not introduced into step S2, and the other steps are the same as Example 1.

[0034] Test experiment 1. Appearance The silicon-carbon composite material in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 2 As shown, Figure 2 is a SEM image of the asphalt-based silicon-carbon composite material provided in Example 1. Figure 2 It can be seen that the material presents a granular structure, and the particle size of the material is evenly distributed, with the particle size ranging from 5 to 10 μm.

[0035] 2. Physical and chemical tests and button cell battery tests Refer to GB / T38823-2020 "Silicon Carbon" to test the specific surface area, tap density and 2T powder compaction density of silicon-carbon composite materials, and use a four-probe tester to test the powder conductivity of silicon-carbon composite materials, and test the gas production of powder materials (add m1g powder material to 45℃ deionized water and soak for 48h to test its gas production V1, and calculate the gas production of powder material = V1 / m1*100%) The silicon-carbon composite materials in Examples 1 to 3 and Comparative Examples 1 to 3 were used as negative electrode materials for lithium-ion batteries to prepare button batteries, and the preparation method was as follows: Add binder, conductive agent and solvent to the composite material, stir to make slurry, coat on copper foil, dry and roll to get negative electrode sheet; the binder used is polyvinylidene fluoride (PVDF), the conductive agent is conductive carbon black (SP), the solvent is N-methylpyrrolidone (NMP), the amount ratio of composite material, SP, PVDF and NMP is 90g:4g:6g:250mL; the electrolyte is lithium hexafluorophosphate (LiPF6), the solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1, and the electrolyte concentration is 1mol / L; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film. The button cell is assembled in an argon-filled glove box.

[0036] The electrochemical performance of button cells comprising the asphalt-based silicon-carbon composite materials of Examples 1 to 3 and Comparative Examples 1 to 3 was tested using a Wuhan Blue Electric CT2001A battery tester with a charge and discharge voltage range of 0.005 V to 2.0 V and a charge and discharge rate of 0.1 C. The rate performance of the material was also tested (1C / 0.1C).

[0037] The thickness D1 of the negative electrode plate of the button battery comprising the asphalt-based silicon-carbon composite materials of Examples 1 to 3 and Comparative Examples 1 to 3 after rolling is tested, and then the button battery is fully charged to 100% SOC and the full-charge thickness D2 of the negative electrode plate is dissected, and then the expansion rate is calculated: the expansion rate is = (D1-D2) / D1.

[0038] The test results are shown in Table 1.

[0039] Table 1. Physical and chemical properties test results of various embodiments and comparative examples It can be seen from the data in Table 1 that the specific capacity, first efficiency, powder conductivity, full charge expansion and DCR of the asphalt silicon-carbon composite material prepared by the present invention are significantly better than those of the comparative example. It can be shown that the present invention improves the electronic conductivity of the material, reduces polarization, and improves the specific capacity and its first efficiency by doping lithium hydride in the asphalt-based porous carbon precursor to generate metallic lithium-doped porous carbon; at the same time, the organic lithium compound coated on the outer layer improves the ion diffusion coefficient of the material, improves the first efficiency and its rate performance. In addition, the use of asphalt-based porous carbon has the characteristics of high compaction density and low impedance, which improves the rate performance.

[0040] 3. Soft pack battery test The pitch-based silicon-carbon composite materials of Examples 1 to 3 and Comparative Examples 1 to 3 were mixed with 95% artificial graphite as negative electrode materials to prepare negative electrode sheets. 1 / 3 Co 1 / 3 Mn 1 / 3 O2) as the positive electrode; lithium hexafluorophosphate (LiPF6) as the electrolyte, a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (DEC) in a volume ratio of 1:1 as the solvent, and an electrolyte concentration of 1.3 mol / L; Celgard 2400 membrane as the separator, and a 5Ah soft-pack battery was prepared. The liquid absorption and retention capacity, rate and high-temperature storage performance of the negative electrode were tested respectively.

[0041] a. Liquid absorption capacity test Use a 1mL burette and draw 1mL of electrolyte, add a drop on the surface of the electrode, and count until the electrolyte is completely absorbed, and record the time t. The test results are shown in Table 2.

[0042] b. Rate and cycle performance The soft-pack batteries including the composite materials of Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to cycle performance tests and rate tests.

[0043] Rate test: Test the constant current ratio of the material under 2C conditions. Constant current ratio = 2C constant current capacity / (2C constant current capacity + 0.1C constant voltage capacity).

[0044] Cycle performance: test voltage range 2.5-4.2V, 1C / 1C, temperature 25±3℃, 500 cycles. The test results are shown in Table 2.

[0045] Table 2 Performance test results of soft-pack batteries made of asphalt-based silicon-carbon composite materials provided in various embodiments and comparative examples It can be seen from Table 2 that the liquid absorption capacity, cycle performance and constant current ratio of the soft-pack lithium-ion battery prepared by the asphalt-based silicon-carbon composite material of the present invention are better than those of the comparative example, which shows that the silicon-carbon composite material of the present invention has a high specific surface area and a low powder resistivity, which improves the liquid retention performance of the battery. At the same time, the embodiment material has low expansion, thereby improving the cycle performance and constant current ratio.

[0046] In general, the asphalt-based silicon-carbon composite material provided in the present invention can improve the electronic conductivity of the material, reduce polarization, and improve the specific capacity and its first efficiency by doping lithium hydride into the asphalt-based porous carbon precursor to generate metallic lithium-doped porous carbon; by coating the outer layer with an organic lithium compound, the ion diffusion coefficient of the material can be improved, and the first efficiency and its rate performance can be improved; the asphalt-based silicon-carbon composite material obtained by the present invention presents a three-layer core-shell structure, which helps to improve the stability and performance of the material.

[0047] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a pitch-based silicon-carbon composite material, characterized in that: The following steps are involved: S1. The raw materials are mixed evenly according to the mass ratio of pitch coke: sodium hydroxide: lithium carbonate = 100: (100-200): (10-50), calcined under a nitrogen atmosphere, washed with mixed acid and deionized water in sequence after calcination, and vacuum dried to obtain pitch-based porous carbon; S2, adding the asphalt-based porous carbon into a vacuum furnace, and introducing heteroatom gas, silane gas, and metal compound gas in stages to obtain a metal-doped silicon-carbon precursor material; S3, heating the metal-doped silicon-carbon precursor material and introducing an oxidizing mixed gas for passivation, and after passivation, immersing it in an organic solvent of an organic lithium compound, mixing it evenly and spray drying it to achieve secondary coating, thereby obtaining the asphalt-based silicon-carbon composite material.

2. The method for preparing the asphalt-based silicon-carbon composite material according to claim 1, characterized in that: In S1, the calcination temperature is 600-1100° C., and the calcination time is 2-6 hours; the mixed acid is hydrochloric acid and nitric acid in a volume ratio of 1:1, and the concentration of the mixed acid is 8-12%.

3. The method for preparing the asphalt-based silicon-carbon composite material according to claim 1, characterized in that: In S2, the specific steps include: S21, adding the asphalt-based porous carbon into a vacuum furnace, introducing nitrogen and maintaining the pressure in the furnace at 1-5 MPa, and introducing heteroatom gas at a flow rate of 50-200 ml / min for 30-300 min when heated to 900-1200° C.; S22, after cooling to 450-550°C, introduce silane gas at a flow rate of 100-500 ml / min for 60-600 min; S23, after heating to 850-1100°C, introduce metal oxide gas at a flow rate of 50-200 ml / min for 60-600 min to obtain a metal-doped silicon-carbon precursor material.

4. The method for preparing the asphalt-based silicon-carbon composite material according to claim 1, characterized in that: In S2, the heteroatom gas is any one of ammonia, hydrogen sulfide, phosphine and borohydride; the silane gas is any one of monosilane, disilane, trichlorosilane and dimethylchlorosilane; the metal compound gas is any one of lithium hydride, magnesium hydride and aluminum hydride.

5. The method for preparing the asphalt-based silicon-carbon composite material according to claim 1, characterized in that: In S3, the temperature of the passivation process is 100-200°C, the introduction rate of the oxidizing mixed gas is 10-100 ml / min, and the passivation time is 30-300 min.

6. The method for preparing the asphalt-based silicon-carbon composite material according to claim 1, characterized in that: In S3, the oxidizing gas is a mixture of any one of O2, O3 and SO2 and nitrogen, and the volume ratio thereof is (1-5):

10.

7. The method for preparing the asphalt-based silicon-carbon composite material according to claim 1, characterized in that: In S3, the organic lithium compound is any one of lithium sulfonate, lithium amide, lithium acetate, lithium stearate and lithium pyruvate; and the organic solvent is any one of propylene carbonate, dimethyl carbonate and diethyl carbonate.

8. A pitch-based silicon-carbon composite material, characterized in that: The asphalt-based silicon-carbon composite material is prepared by the preparation method of any one of claims 1 to 7.

9. The asphalt-based silicon-carbon composite material according to claim 8, characterized in that: The asphalt-based silicon-carbon composite material has a three-layer core-shell structure, wherein the core is a metal-doped silicon-carbon material, the middle layer is silicon dioxide, and the outer shell is an organic lithium compound, comprising the following mass ratio of the core: middle layer: outer shell = (93~98.5): (0.5~2): (1~5).

10. A lithium ion battery, characterized in that: Including the asphalt-based silicon-carbon composite material as described in claim 9.

Citation Information

Patent Citations

  • Method for preparing silicon-carbon composite material based on silane cracking method and application of silicon-carbon composite material

    CN118117071A

Cited By

  • Porous carbon material applied to silicon-carbon negative electrode as well as preparation method and application of porous carbon material

    CN120191930A